PEMANFAATAN DAPODIK SEBAGAI SISTEM INFORMASI PENDIDIKAN DALAM PENGELOLAAN DATA AKADEMIK DI SMA NEGERI 12 GOWA - Sahrul, Sahrul; Damopolii, Muljono; Hasan, Mardhiah (Department of Islamic Education Management, 2026)
The urgency of this research is based on the importance of optimizing the utilization of Dapodik as an educational information system that supports accurate, integrated, and sustainable academic data management. This study aims to analyze the utilization of the Basic Education Data System (Dapodik) as an educational information system in academic data management at SMA Negeri 12 Gowa. This research employed a descriptive qualitative approach with purposively selected informants consisting of Dapodik operators, teaching staff, and education personnel. Data were collected through semi-structured interviews and direct observation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that Dapodik has been utilized as an educational information system for managing academic data at SMA Negeri 12 Gowa. Its utilization improves data validity, administrative efficiency, report preparation, and data-based decision-making. However, several challenges remain, including limited internet connectivity, server maintenance issues, and delays in data updates. Therefore, improving operator competency, strengthening coordination among school members, and providing adequate technological infrastructure are necessary to optimize the use of Dapodik in academic data management. This study implies that effective utilization of Dapodik requires not only a reliable information system but also human resource readiness and institutional support to improve the quality of academic data management.